Social Participation Through Volunteering as Co-production of Public Services: Case Study of Latvia - Putans, Romans; Starineca, Olga; Voroncuka, Inese (University of Latvia, 2016)
Active civic and social participation is considered to be significantly important for a country`s development in democratic societies. One of the popular forms of active citizenship is volunteering – the third economy sector that produces civic goods and/or services in which the public and private sectors are weak or inactive. In this aspect, volunteering is also a means for organized civil society to participate in the production of public services i.e. co-production. The aim of this research is the exploration of social participation in Latvia through volunteering, including its legal regulation and organizational setup, and identification of the aspects and prospects of volunteering in Latvia within the concept of co-production of public services. The research is exploratory by design. The main methods of the study applied are analysis and synthesis. Volunteering in Latvia is yet on its way to being considered a valuable part of general active citizenship and social participation, and admittedly even further from being a serious part of co-production. Compared to other European countries, volunteering in Latvia is a new way of social participation that mostly attracts youth and seniors. Volunteering is only a relatively recent recognized activity in Latvia, however this sector of economy is developing and has its achievements. The current research has both theoretical and practical application. The study is organised within the framework of the EU program’s “Europe for Citizens” international project “Volunteering – Code of Active Citizenship” implemented in cooperation with six partners from different EU member states under the leadership of Kaunas University of Technology.
Keywords: Research Subject Categories::SOCIAL SCIENCES; Volunteering; Social participation; Active Citizenship; Co-production; Public good